High-Density Genetic Mapping Identifies New Susceptibility Variants in Sarcoidosis Phenotypes and Shows Genomic-driven Phenotypic Differences - Rivera, Natalia V; Ronninger, Marcus; Shchetynsky, Klementy; Franke, Andre; Nöthen, Markus M; Müller-Quernheim, Joachim; Schreiber, Stefan; Adrianto, Indra; Karakaya, Bekir; van Moorsel, Coline H M; Navratilova, Zdenka; Kolek, Vitezslav; et al. (American journal of respiratory and critical care medicine, 2016)
RATIONALE: Sarcoidosis is a multisystem disease of unknown cause. Löfgren's syndrome (LS) is a characteristic subgroup of sarcoidosis that is associated with a good prognosis in sarcoidosis. However, little is known about its genetic architecture or its broader phenotype, non-LS sarcoidosis. OBJECTIVES: To address the genetic architecture of sarcoidosis phenotypes, LS and non-LS. METHODS: An association study in a white Swedish cohort of 384 LS, 664 non-LS, and 2,086 control subjects, totaling 3,134 subjects using a fine-mapping genotyping platform was conducted. Replication was performed in four independent cohorts, three of white European descent (Germany, n = 4,975; the Netherlands, n = 613; and Czech Republic, n = 521), and one of black African descent (United States, n = 1,657), totaling 7,766 subjects. MEASUREMENTS AND MAIN RESULTS: A total of 727 LS-associated variants expanding throughout the extended major histocompatibility complex (MHC) region and 68 non-LS-associated variants located in the MHC class II region were identified and confirmed. A shared overlap between LS and non-LS defined by 17 variants located in the MHC class II region was found. Outside the MHC region, two LS-associated loci, in ADCY3 and between CSMD1 and MCPH1, were observed and replicated. CONCLUSIONS: Comprehensive and integrative analyses of genetics, transcription, and pathway modeling on LS and non-LS indicates that these sarcoidosis phenotypes have different genetic susceptibility, genomic distributions, and cellular activities, suggesting distinct molecular mechanisms in pathways related to immune response with a common region.
Keywords: Genetic Predisposition to Disease; genotyp; genomika; Genotype; Česká republika; Sarcoidosis, Pulmonary; plicní sarkoidóza; Netherlands; Middle Aged; United States; mužské pohlaví; Německo; Sweden; fenotyp; Löfgren’s syndrome; Czech Republic; genetic epidemiology of sarcoidosis; Phenotype; ženské pohlaví; Genomics; Humans; Spojené státy americké; Germany; genome-wide associations; lidé středního věku; non-Löfgren’s syndrome; genetická predispozice k nemoci; Švédsko; Female; Immunochip; lidé; Male; Nizozemsko